The Idea of Abdel Moneim Hassan Al-Malik in Teaching Arabic as a Second Language - Elmakki Abdu Rahim Elmakki Mohameed (Journal of Arabic Language Studies and Teaching, 2022)
This study discusses the application and testing of the idea of Abdel Moneim Hassan Almalik, through the applied descriptive approach, at the Institute of Teaching Arabic as a second language. This paper dealt with the importance of each skill of the Arabic language for non-native speakers, as well as presenting and analyzing the idea and comparing the communicative attitudes in the idea with the communicative attitudes in the Sudan Open University series. A table was put in to compare the foundations and principles of the idea with the study sample. It also dealt with the presentation of the teaching steps with the notion, and this paper has chosen the students of the Institute of Arabic Language as a second language at the Open University of Sudan to experiment on them. The study revealed the importance and the possibility of applying this idea to various series of teaching Arabic, provided that it is a second language, besides focusing the idea on the skills as a whole, where none of the four skills is neglected. On the other hand, the teacher is trained to compose by writing advanced texts for each lesson. This model reinforces what he learned and is a foundation to build on. It helped the student remember vocabulary. At the same time, some began to ask questions stemming from the comparison between classical and Sudanese dialects. This resulted in the focus of this model on linguistic correctness.